Effect of Structural Parameters on Compression Performance of Warp-knitted Spacer Fabric (Journal of Fiber Bioengineering and Informatics, 2015)
The main content dealt with in the paper is to analyze effects of structural parameters on compression\rproperty of spacer fabrics. Based on compression stress and strain curves, four characteristic indices are\rfeatured, which include compression work, recovery ratio of compression work, maximum compression\rforce when compression strain is 0.7 and secant modulus by fitting compression stress - strain curve\rfrom strain 0 to 0.25. Experimental results show that structural parameters of spacer fabric, including\rthickness of spacer fabric and diameter, angle, arrangement shape and density of spacer filament,\rsignificantly influence compression behaviour. With the thickness of specimen increasing, compression\rwork increased, while the compression secant modulus and maximum force decreased, and the recovery\rexisted nonlinear relationship and showed a relatively optimal thickness. Compression work, recovery\rratio, maximum force and secant modulus existed the same ascending trend when the diameter of spacer\rfilament increased from, while they showed descending trend when spacer angles decreased. The whole\rstructure of spacer fabric was more stable when the arrangement of spacer filament is X-shaped than Vshaped,\rand the compression work, recovery ratio, maximum force and secant modulus of sample X shape\rwere all larger than those of sample V shape. As for the density of spacer filaments, the compression\rwork, maximum force and secant modulus increased with density decreased, while the recovery ratio of\rspacer fabric with higher density was smaller than that of smaller density.